Discolored1 (DSC1) is an ADP-Ribosylation Factor-GTPase Activating Protein Required to Maintain Differentiation of Maize Kernel Structures - Takacs, Elizabeth M.; Suzuki, Masaharu; Scanlon, Michael J. (Frontiers in Plant Science, 2012)
The embryo and endosperm are the products of double fertilization and comprise the clonally distinct products of angiosperm seed development. Recessive mutations in the maize gene DISCOLORED1 (DSC1) condition inviable seed that are defective in both embryo and endosperm development. Here, detailed phenotypic analyses illustrate that dsc1 mutant kernels are able to establish, but fail to maintain, differentiated embryo and endosperm structures. Development of the dsc1-R mutant embryo and endosperm is normal albeit delayed, prior to the abortion and subsequent degeneration of all differentiated kernel structures. Using a genomic fragment that was previously isolated by transposon tagging, the full length DSC1 transcript is identified and shown to encode an ADP-RIBOSYLATION FACTOR-GTPase ACTIVATING PROTEIN (ARF-GAP) that co-localizes with the trans-Golgi network/early endosomes and the plasma membrane during transient expression assays in N. benthamiana leaves. DSC1 function during endomembrane trafficking and the maintenance of maize kernel differentiation is discussed.